Authenticity between pure theory and practical application – the barrier of words - Adrian Crăciunescu (Ochrona Dziedzictwa Kulturowego)
The theory on authenticity can generate disputes depending to the geographical and cultural space of those who define this concept. It seems, however, that this ideological dispute (see the Petzet-Araoz dialogue), tends to remain an abstraction related to the material and immaterial, ignoring some pragmatic elements that are at the root of the cultural misunderstandings related to the authenticity of heritage. I have selected three of them that I consider to be essential.